A van der Pol-like complementary chaotic oscillator: Design, physical realizations, dynamics, and physiological data augmentation prospect - Ngamsa Tegnitsap, Joakim Vianney; Tabekoueng Njitacke, Zeric; Barà, Chiara; Fonzin Fozin, Théophile; Fotsin, Hilaire Bertrand; Valdes-Sosa, Pedro Antonio; Yoshimura, Natsue; Minati, Ludovico (Chaos, solitons and fractals, 2025)
This study proposes a van der Pol-like complementary chaotic oscillator circuit. By exploiting components from both semiconductor and vacuum tube technologies, specifically field-effect transistors and triodes, different physical realizations of this oscillator are achieved. The proposed design is an asymmetric cross-coupled complementary circuit derived from the classical van der Pol oscillator coupled to a linear circuit. This study explores the unique physical properties of the nonlinear amplifying elements and the resulting dynamic behaviors of the systems, systematically comparing their characteristics from a dynamical perspective and initially investigating their applicability to physiological data augmentation. First, a detailed analysis of the effects of the nonlinearities of each device on the system behavior is performed, revealing that triodes lead to smoother and more stable oscillations, including weak chaos due to torus breakdown, whereas field effect transistors lead to more disordered chaotic oscillations, accompanied by strong hysteresis, coexistence of attractors, and unstable oscillations. Then, for each amplifier device, the corresponding oscillator is driven by representative physiological signals, including electroencephalograms, electrocardiograms, electromyograms, and plethysmograms, thus harnessing the system response to the disturbance and gaining insights into its ability to enhance data, qualitatively through spectrograms and quantitatively by means of information theoretical measurements. This work illustrates the possibility of harnessing the nonidealities of diverse existing physical devices towards nonlinear signal processing. •A van der Pol-like complementary chaotic oscillator was designed and realized using triodes and JFETs transistors.•The qualitative features of the dynamics were largely consistent across the equation and SPICE models and experiments.•Triodes produced stable, smooth oscillation with weak chaos, whereas FETs more disordered activity.•The side-by-side comparison of different circuit realizations illustrated the effect of physical non-idealities.•The possible relevance of circuits of this kind in the data augmentation of physiological signals (EEG, ECG) was exemplified.